Transformation of Traditional Competitive Advantages of Companies within Ensuring the Economic Security - POLOVOVA, Tatyana A.; GLADILINA, Irina P.; GUSEV, Yuri V.; POGUDAEVA, Marina Yu.; KOLESNIK, Vladimir V. (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The paper opens up the etymology of the economic category ‘competitive advantages’. The main problems in treating them and in the main economic schools' forming the competitiveness are discussed in order to form a holistic idea about the conceptual model of strategically managing the competitive advantages of companies as social and economic systems. Systemic and comparative analysis, methods of observation and graphical data presentation, systematization and information methods have been used for grounding the authors' approach to the formation of competitive advantages and to selecting the competitiveness strategy within the context of transformation of the competitive advantages. After processing of the materials, the main directions of the competitive advantages transformation for Russian companies were put forward. This has allowed forming the idea about the companies being competitive at the global market. The aspiration to ensure the competitiveness for companies at the global market for keeping their economic security underlies the formation of competitive advantages. As a result of the research, the authors have attempted to determine a structure that would completely reflect the directions for the formation of competitive advantages in order to ensure the economic security as well. The competitive advantages are singled out as an isolated category having the functions of goal orientation that allows estimating the condition of competitiveness shifts. This gives grounds for stating that competitive advantages are an indicator of both quantitative and qualitative change in the development of companies. The research results have been elaborated up to the point of concept provisions, which grants opportunities for applying it in developing a technique for strategic assessment of the competitiveness of companies.